Legislation on insurance contracts - some inadequacies and recommendations for finalization - Tran, Linh Huan; Pham, Thi Hong Tam (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2023)
The insurance contract is an agreement between the policyholder and the insurance company, in which the policyholder pays insurance premiums, and the insurance company pays insurance benefits to the beneficiary or compensates the insured party in the event of an insured event. Insurance contracts play a crucial role in recording and establishing the rights and obligations of the parties involved in the insurance relationship. Currently, the Law on Insurance Business of 2022 has introduced some adjustments regarding this type of contract; however, it has not been fully perfected. Building on this premise, this article focuses on analyzing and assessing certain limitations and shortcomings in the legal regulations pertaining to insurance contracts based on the Law on Insurance Business 2022. Subsequently, it presents recommendations for improvement.